EXPLORING THE ROLE OF FORESTRY SECTOR ON ECONOMIC SYSTEM OF GUNUNGKIDUL DISTRICT IN 1993 - 2008 - Rahmat, Mamat; F., Takahiro; Sato, Noriko (Secretariat of Forestry Research and Development Agency, 2012)
This study was conducted to explore the role of forestry sector in the economic system of Gunungkidul district. The Location Quotient (LQ) Analysis, Income Multiplier Effect Value, and Klassen Typology Analysis were employed to analyze the role of the forestry sector. The data were regional income of Gunungkidul district and Yogyakarta Province from 1993 to 2008, including the economic crisis period from 1997 to 1998. The result showed that forestry sector was an important sector in economic development of Gunungkidul district. LQ analysis indicated that forestry became a basic sector since pre-economic crisis period until post-economic crisis (1993 - 2008). Prior to the economic crisis, forestry sector generated the highest income multiplier effect value. However, the value dropped during and after the economic crisis. The economic crisis had an influence on the development pattern classification of forestry sector. Before economic crisis, forestry sector was classified as a developed sector (quadrant I) with the growth and shared to GDRP in Gunungkidul were higher than that in Yogyakarta Province. Meanwhile, since the economic crisis, forestry sector fell into the lower class as a stagnant sector.